Using Canva to Create Visual Materials in Mathematics Education - Santoso, Hajar Ahmad; Istiqomah, Nisa Rachmi (Universitas Negeri Surabaya, 2022)
The research aims to create innovative learning e-modules in circle equation material. This module is designed using the Canva application which provides an attractive and interactive display. After development, the module has been tested to ensure its quality. The trial was carried out in two stages. The first stage involved 2 expert validators in their fields. The second phase involved 30 students from SMAN 3 Sidoarjo. The module development process followed the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. The trial results show that this module is suitable for use as an effective teaching material to help students in the learning process. This results show that can helping students to find the circle equation material themselves, associating the material with issues that are currently being discussed in students' lives so that it attracts their interest, equipped with interesting pictures and an aesthetic appearance, and providing flexibility and convenience for teachers to make further revisions and developments according to learning needs and developments.